2014
DOI: 10.1016/j.bbamcr.2014.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of calcium-induced cell death in human neural stem cells by the novel peptidylarginine deiminase–AIF pathway

Abstract: PADs (peptidylarginine deiminases) are calcium-dependent enzymes that change protein-bound arginine to citrulline (citrullination/deimination) affecting protein conformation and function. PAD up-regulation following chick spinal cord injury has been linked to extensive tissue damage and loss of regenerative capability. Having found that human neural stem cells (hNSCs) expressed PAD2 and PAD3, we studied PAD function in these cells and investigated PAD3 as a potential target for neuroprotection by mimicking cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 66 publications
(56 reference statements)
1
43
0
Order By: Relevance
“…PADs have been shown to be upstream regulators of Ca 2+ -induced cell death in human neural cells, and PAD inhibition protects cells from apoptosis by hindering calcium-induced cytoskeleton disassembly [15]. The present in vitro findings are in accordance with a previous study in a murine model of ischemic insult where pan-PAD inhibition resulted in significantly reduced apoptotic cell death [16].…”
Section: Discussionsupporting
confidence: 90%
“…PADs have been shown to be upstream regulators of Ca 2+ -induced cell death in human neural cells, and PAD inhibition protects cells from apoptosis by hindering calcium-induced cytoskeleton disassembly [15]. The present in vitro findings are in accordance with a previous study in a murine model of ischemic insult where pan-PAD inhibition resulted in significantly reduced apoptotic cell death [16].…”
Section: Discussionsupporting
confidence: 90%
“…PAD1 targets keratin and filaggrin [7]; PAD2 targets myelin basic protein (MBP) [30], vimentin [42], actin, and histones [39]; PAD 3 targets filaggrin, trichohyalin [7], apoptosis-inducing factor (AIF), and vimentin [43]; PAD4 targets multiple proteins involved in gene regulation (histones [24, 44], inhibitor of growth 4 (ING4) [45], p300 [46], p21 [47]) and apoptosis (nucleophosmin [48], nuclear lamin C [49]) ; and there are no known protein substrates of PAD6 (Table 1) [35]. Several of these protein targets of PAD citrullination will be described throughout the next sections that have a high arginine content (~10%) and/or have particular arginine-rich regions that are critical for their structure and function.…”
Section: The Protein Arginine Deiminase Family Of Enzymesmentioning
confidence: 99%
“…Additionally, Mizoguchi et al (1998) reported the citrullination of a 70kDa nuclear protein localized on the periphery of the nucleus was linked to dissociation of the nuclear lamina during apoptosis [58]. Recently, PAD3 was found to be necessary for apoptosis-inducing factor (AIF)-mediated apoptosis [43]. Overall, PAD activation (due to amplified calcium levels during the early stages of apoptosis) can facilitate apoptotic cell death by citrullinating several nuclear and cytoskeletal proteins that can cause structural changes resulting in the disintegration of secondary and tertiary protein structures [6, 18, 19].…”
Section: Normal Pad Functionmentioning
confidence: 99%
“…PAD2 is expressed in the retina and optic nerve of patients with glaucoma [22] and increased in age-related macular degeneration [24]. PAD3 is expressed in human neural stem cells [25], and PAD4 is found in the brains of Alzheimer’s [26] and multiple sclerosis [27] patients. However, it remained unknown which PAD enzyme is overactive in injury-induced gliosis.…”
Section: Introductionmentioning
confidence: 99%